2x-(x-5)+3(x-1)=12

Simple and best practice solution for 2x-(x-5)+3(x-1)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(x-5)+3(x-1)=12 equation:


Simplifying
2x + -1(x + -5) + 3(x + -1) = 12

Reorder the terms:
2x + -1(-5 + x) + 3(x + -1) = 12
2x + (-5 * -1 + x * -1) + 3(x + -1) = 12
2x + (5 + -1x) + 3(x + -1) = 12

Reorder the terms:
2x + 5 + -1x + 3(-1 + x) = 12
2x + 5 + -1x + (-1 * 3 + x * 3) = 12
2x + 5 + -1x + (-3 + 3x) = 12

Reorder the terms:
5 + -3 + 2x + -1x + 3x = 12

Combine like terms: 5 + -3 = 2
2 + 2x + -1x + 3x = 12

Combine like terms: 2x + -1x = 1x
2 + 1x + 3x = 12

Combine like terms: 1x + 3x = 4x
2 + 4x = 12

Solving
2 + 4x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 4x = 12 + -2

Combine like terms: 2 + -2 = 0
0 + 4x = 12 + -2
4x = 12 + -2

Combine like terms: 12 + -2 = 10
4x = 10

Divide each side by '4'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| (6n^2-5n^3)+(n^3+5n^2)=0 | | -(2/3)*-5 | | √10/81 | | (6)(-3)+2(55-65)/-5= | | x(y^5+9)+9(y^5+9)= | | q(6-2q)=0 | | 50-30+80=-60 | | 3(u-5)-7=-2(-8u+8)-3u | | 2x^2-33x+108=5123 | | x*.0635=1000 | | 4x^2-13x+13=5x+10 | | x*6.35=1000 | | =-5x+30 | | 0.75x-3=0.25x+7 | | -2(w+2)=2w-32 | | 100x+50(12-x)=950 | | x^2-10x-40=-5x-4 | | 3x+3(2x)=146 | | x^2-x-5=1 | | x^2+x-23=2x-3 | | 6y+45=-9(y+5) | | Y=x^4+2x^3+4x^2+8x+1 | | 9/15/2/4= | | 2-b-4a+2ab=0 | | 4w+30=-2(w+6) | | a=3b+4 | | 5x-5=3(x-1) | | 2x^2+lax+2=0 | | H=16t^2+4t | | a=5b+1 | | 6331/x=0.13 | | 1316=x*(19+x) |

Equations solver categories